Effect of Early Balance Exercise on Dependency Level in Patients with Stroke - Suror Khalil Ibrahim; Dr. Hassan Abdullah Athbi (Migration Letters, 2023)
Background: Stroke is the primary global factor contributing to adult disability. It is minimizing the patient’s ability to carry out everyday activities; 40% of patients with stroke have total dependence to carry out daily activities six months after a stroke. Trunk function and sitting balance are essential components of recovery following a stroke. Objective: The aims of the present study is to identify the effect of early sitting balance exercises on the level of dependency in patients with stroke. Methods: A quasi-experimental study was performed at Imam Al-Hussein Medical City from September 26th, 2022, to June 13th, 2023. A non-probability purposive sampling consisted of sixty patients with acute stroke; they were divided into control and intervention groups. Patients in the intervention group were instructed to perform five balance exercises for 15–30 minutes/two sessions per day for 14th days. These exercises include shifting weight from side to side, reaching, seated leg lifts, single-leg knee extensions, and reaching with clasped hands. While patients in the control group just received routine medical treatment. The study instrument consisted of two main parts: part one included patient’s socio-demographics and medical data, and the second part was used to assess the level of dependency using a Modified Barthel index that consists of 10 items. Both a descriptive analysis procedure and an inferential analysis procedure (e.g., independent sample T-test, and paired sample T-test) were used to investigate and measure the study results; a p-value of <0.05 was detected to be statistically significant. Results: Most patients (86.7%) in the intervention group had a severe dependency level in the pre-test, while at the post-test period, 53.3%, 20%, and 20% of patients in the intervention group had moderate dependency levels, slight dependence, and independence, respectively. A significant statistical difference at a p value of 0.001 was found between the control and intervention groups after the performance of sitting balance exercises. Conclusion: The performance of early sitting balance exercises post-stroke for 15–30 minutes, two sessions per day for 14 days, significantly decreases dependency levels and achieves independence in a person’s activities of daily living.